NETTLE DIOECIOUSLY (URTICA DIOICA L.) AND LICORICE (GLYCYRRHIZA GLABRA L. ) STANDARDIZATION OF CAPSULES BASED ON DRY EXTRACTS (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2023)
A comprehensive study of the aboveground part of plants of the genus Urtica (dioeciously nettle, hemp nettle, stinging nettle) growing on the territory of the Uzbekistan and Altai Territory is carried out. Dry extracts were obtained from the herb of nettle dioeciously, the herb of nettle hemp, the herb of nettle burning. When studying the technological properties of dry hemp nettle grass extract, high dampness was established, so it became necessary to develop the composition of the encapsulated form with the addition of auxiliary substances.